Message in a vesicle - trans-kingdom intercommunication at the vector-host interface - Chávez, Adela S Oliva; O'Neal, Anya J; Santambrogio, Laura; Kotsyfakis, Michail; Pedra, Joao H F (Journal of cell science, 2019)
Vector-borne diseases cause over 700,000 deaths annually and represent 17% of all infectious illnesses worldwide. This public health menace highlights the importance of understanding how arthropod vectors, microbes and their mammalian hosts interact. Currently, an emphasis of the scientific enterprise is at the vector-host interface where human pathogens are acquired and transmitted. At this spatial junction, arthropod effector molecules are secreted, enabling microbial pathogenesis and disease. Extracellular vesicles manipulate signaling networks by carrying proteins, lipids, carbohydrates and regulatory nucleic acids. Therefore, they are well positioned to aid in cell-to-cell communication and mediate molecular interactions. This Review briefly discusses exosome and microvesicle biogenesis, their cargo, and the role that nanovesicles play during pathogen spread, host colonization and disease pathogenesis. We then focus on the role of extracellular vesicles in dictating microbial pathogenesis and host immunity during transmission of vector-borne pathogens.
Keywords: Trypanosomiasis; Psychodidae; filarióza; Exosomes; Amebiasis; extracelulární vezikuly; Immunomodulation; Virus Diseases; členovci - vektory; Host-Parasite Interactions; interakce hostitele a parazita; virové nemoci; trypanozomiáza; Arthropod Vectors; Vector Borne Diseases; Leishmaniasis; Disease Vectors; exozómy; Cell communication; imunomodulace; nemoci přenášené vektory; Filariasis; Hemiptera; Extracellular Vesicles; Animals; Arthropod-borne disease; lidé; Extracellular vesicle; malárie; Humans; zvířata; Culicidae; infekce přenášené vektorem; Malaria; leishmanióza; Microbial transmission; amébiáza